2002
DOI: 10.1093/jaoac/85.6.1390
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vegetal Proteins in Milk Powder by Enzyme-Linked Immunosorbent Assay: Interlaboratory Study

Abstract: Eight laboratories participated in a collaborative study to evaluate an enzyme-linked immunosorbent assay (ELISA) to determine soy, pea, and wheat proteins in pasteurized or ultra-high temperature (UHT) milk powders. To perform this assay, polyclonal antibodies for soy, pea, and wheat proteins were obtained from rabbit sera. Collaborators received calibration standards composed of milk powder containing 0–8% (w/w) vegetal protein in total protein and blind test samples containing approximately 1, 2, and 5% (w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Particularly, such supplementation happens when the supply of raw milk is not sufficient in the summer as consumer demand increases and cow milk production decreases. Because the ultra-heat treatment procedure has been widely used in preparing milk powder, efforts using heat-denatured milk proteins as bioindicators have been extended to detect false practices (Relkin, 1996;Sanchez et al, 2002;Steffensen et al, 2002). For example, Recio and Olieman (1996) showed that the amount of heat-denatured proteins could be estimated by analyzing the casein fraction using capillary zone electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, such supplementation happens when the supply of raw milk is not sufficient in the summer as consumer demand increases and cow milk production decreases. Because the ultra-heat treatment procedure has been widely used in preparing milk powder, efforts using heat-denatured milk proteins as bioindicators have been extended to detect false practices (Relkin, 1996;Sanchez et al, 2002;Steffensen et al, 2002). For example, Recio and Olieman (1996) showed that the amount of heat-denatured proteins could be estimated by analyzing the casein fraction using capillary zone electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of plant or animal origin could be added to milk, a practice that is common in countries if they are cheaper than milk proteins. A number of electrophoretic (Kanning et al, 1993;Cattaneo et al, 1994;López-Tapia et al, 1999;Manso et al, 2002a,b), chromatographic (Cattaneo et al, 1994;Espeja et al, 2001) and immunochemical (Turin & Bonomi, 1994;Sánchez et al, 2002) methods have been used to detect the addition of non-dairy protein in milk products.…”
Section: Addition Of Non-dairy Proteinsmentioning
confidence: 99%
“…Added soy, pea, and soluble wheat protein in milk powder could be detected through immunological tests. Development of polyclonal antibodies in immunoassays has made it possible to detect these adulterants in a range of 1-5% of plant protein in the total milk protein content, although the results seem to be significantly affected by ultra-high temperature (UHT) treatment applied to the samples (Haasnoot et al 2001;Sanchez et al 2002). Compared with Enzyme-Linked Immunosorbent Assay (ELISA), the results of vegetable protein percentages obtained from Sodium Dodecyl Sulfate-Capillary Electrophoresis (SDS-CE) had a higher rate of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Enzyme-Linked Immunosorbent Assay (ELISA), the results of vegetable protein percentages obtained from Sodium Dodecyl Sulfate-Capillary Electrophoresis (SDS-CE) had a higher rate of accuracy. However, due to its poor reproducibility, SDS-CE requires improvement in terms of instrument and operation standardisation before large-scale use is feasible (Sanchez et al 2002). The application of mass spectroscopy (MS) allowed the identification of plant protein added to milk powder.…”
Section: Introductionmentioning
confidence: 99%